Effect of bio-stimulant and nitrogen levels on growth and productivity of kharif rice - Naveen, P V; Maitra, S; Chhetri, P; Masina, S; Dash, B; Ray, S (Plant Science Today, 2026)
Kharif rice (Oryza sativa L.) production systems in India frequently encounter challenges, including erratic monsoon patterns, declining soil fertility and imbalanced nutrient management. This field experiment was carried out to evaluate the synergistic influence of foliar-applied seaweed-based bio-stimulant (Kappaphycus alvarezii sap) and graded nitrogen doses on the growth and productivity of kharif rice (cv. RNR-15048). The experiment was arranged in a split-plot design with three nitrogen doses (0, 60 and 120 kg ha) in main plots and four bio-stimulant doses (0, 5, 10 and 15 mL L-1) as sub-plots which were replicated thrice. The results revealed significant improvements in growth attributes at different growth stages of rice. Yield components such as panicle bearing tillers m-2, panicle length (cm), filled grains panicle-1 and 1000-grain weight (g) were also significantly influenced due to the application of bio-stimulants and varied nitrogen levels. In case of bio-stimulants, the treatment with 15 mL L-1 K. alvarezii sap produced the highest grain and stover yield (3.8 t ha-1 and 4.8 t ha-1, respectively) and with regards to nitrogen levels, application of 120 kg ha-1 of N recorded the maximum grain yield (4.1 t ha-1) and stover yield (5.1 t ha-1) of rice. The findings demonstrate that integrating bio-stimulant application at of 15 mL L-1 with an appropriate nitrogen level of 120 kg ha-1 can improve the growth and productivity of kharif rice.